2014
DOI: 10.1124/dmd.114.058602
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Calibration Curve–Based Approaches to Predict Clinical Inducers and Noninducers of CYP3A4 with Plated Human Hepatocytes

Abstract: Cytochrome P450 (P450) induction is often considered a liability in drug development. Using calibration curve-based approaches, we assessed the induction parameters R 3 (a term indicating the amount of P450 induction in the liver, expressed as a ratio between 0 and 1), relative induction score, C max /EC 50 , and area under the curve (AUC)/F 2 (the concentration causing 2-fold increase from baseline of the doseresponse curve), derived from concentration-response curves of CYP3A4 mRNA and enzyme activity data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
42
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 39 publications
7
42
1
Order By: Relevance
“…Several publications have highlighted the utility of 2D or sandwich-cultured models using cryopreserved human hepatocytes to assess the CYP3A4-induction-based drug-drug interaction (DDI) risk of new chemical entities (NCEs) by conducting retrospective analyses on compounds that are known to be CYP3A4 inducers or noninducers in the clinic (Fahmi et al, 2010;Einolf et al, 2014;Zhang et al, 2014). Although these models have proven to be invaluable in understanding the CYP3A4-induction-based DDI risk of NCEs in both a practical and cost-effective way, the 2D substratum forces hepatocytes to alter their cytoskeleton toward a flattened morphology (Buxboim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several publications have highlighted the utility of 2D or sandwich-cultured models using cryopreserved human hepatocytes to assess the CYP3A4-induction-based drug-drug interaction (DDI) risk of new chemical entities (NCEs) by conducting retrospective analyses on compounds that are known to be CYP3A4 inducers or noninducers in the clinic (Fahmi et al, 2010;Einolf et al, 2014;Zhang et al, 2014). Although these models have proven to be invaluable in understanding the CYP3A4-induction-based DDI risk of NCEs in both a practical and cost-effective way, the 2D substratum forces hepatocytes to alter their cytoskeleton toward a flattened morphology (Buxboim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One caveat of including BSA in induction medium is that it can lower the concentration of free drug. Although inducer depletion and binding have previously been accounted for in induction predictions (Zhang et al, 2014;Chang et al, 2016), to date, no comprehensive study has been conducted to systematically investigate the impact of binding and depletion on induction predictions across multiple inducers and prediction methods. In the current evaluation, we sought to determine the measured and free concentrations of six clinical inducers and one noninducer of CYP3A4 in hepatocyte culture medium, and determine whether correction for these parameters can improve the accuracy of CYP3A4 induction predictions.…”
Section: Discussionmentioning
confidence: 99%
“…introduction Drug-drug interactions (DDIs) related to CYP3A4 induction remain a concern for the pharmaceutical industry given that induction can affect the safety and efficacy of coadministered drugs (Lin, 2006;Zhang et al, 2014). Typically, the concentration-response data used in these models rely on the nominal concentration of the applied new chemical entities (NCEs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, drug interaction knowledge might increase efficacy of a drug and reduce its undesirable side effects and toxicity. According to the US Food and Drug Administration (FDA) and European Medicines Agency (EMA) guidelines for drug–drug interactions, the effect of a drug on CYP mRNA levels in fresh or cryopreserved human hepatocytes is critical for CYP-induced drug interactions 28,29. Numerous drug–drug interaction studies using primary or cryopreserved human hepatocyte culture systems have been reported 3035…”
Section: Introductionmentioning
confidence: 99%